Implikasi Yuridis Perubahan Nama Laut Natuna Utara terhadap Zona Ekomoni Eksklusif Indonesia (ZEEI) Ditinjau dari Hukum Internasional - Rizky Hidayatullah; Chomariyah; Dita Birahayu (Faculty of Law Hang Tuah University, 2018)
Indonesia changes the name of the sea in its Exclusive Economic Zone, which initially changed the name of the South China Sea to North Natuna Sea. The change in the name of the North Natuna Sea in Indonesia was protested by the Chinese government, given the abundant natural resources that made other countries especially China want to seize this region. Not only that, the North Natuna Sea is also one of the legal conflicts. The Indonesian government must increase awareness in terms of security and national defense in protecting sovereignty, especially in the North Natuna Sea. This study uses a normative juridical method and uses a legislative approach, a case approach, and a conceptual approach in this case literature study of library materials so that it can be called library legal research. The impact of the change in the name of the North Natuna Sea internally, the change in the map of Indonesia in the North Natuna Sea because this change can be implemented without external parties. External impact, Indonesia received recognition from other countries that the name of the Indonesian sea has changed its name. And efforts made by Indonesia to secure the stability of the North Natuna Sea.